Slip flow of magnetite-water nanomaterial in an inclined channel with thermal radiation. (March 2017) - Abbas, Z.; Rahim, T.; Hasnain, J.
Abstract: An analytic study is performed to analyze the mixed convective two phase flow of magnetite-water (ferrofluid) and viscous fluid in an inclined channel with velocity slip at the walls in the presence of thermal radiation. The channel, separated in two phases, is suffused with a viscous fluid in upper phase and an electrically conducting ferrofluid in the lower phase. Fully developed flow conditions are considered while developing the flow equations. The obtained ordinary differential equations are solved using an analytic approach named as Perturbation method. The numerical values of the results are plotted to interpret the influence of numerous pertinent parameters on flow fields. The results show an increase in the fluid velocity with the hike in velocity slip parameters whereas the fluid velocity decreases with an increase in ferroparticles volume fraction. It is also found that the radiation reduces the impact of natural convection by reducing the temperature difference between the fluid and the walls of the channel. Highlights: Two-Phase flow of magnetite-water (ferrofluid) and viscous fluid is modeled. Slip condition at the walls of inclined channel is investigated. Magnetoconvection effects with linear radiative heat transfer. Analytical approach is used to solve nonlinear differential equations.